Funkcja, działalność i usługi informacyjne – terminy z zakresu bibliologii i informatologii na polu archiwistyki - Cołbecka, Monika (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
This article is a continuation of research and a deeper study of archivists’ current understanding of concepts drawn from bibliology and information science theory. Starting with a discussion of the similarities between these academic disciplines, the following terms will be discussed: the informational function, informational activities, and informational services of archives. In order to distinguish between them, the author traced the context in which they have so far appeared in bibliological, informological, and archival literature, even without the accompanying adjective “informational”. The result of such an analysis is the definition of these terms for archival science and a precise delineation of the boundaries between them.